Morphological, functional and neurological outcomes of craniectomy versus cranial vault remodeling for isolated nonsyndromic synostosis of the sagittal suture: a systematic review. (September 2015) - Thwin, May; Schultz, Timothy J; Anderson, Peter J
Executive summary : Background : Craniosynostosis is a condition characterized by the premature closure of one or more of the cranial vault sutures. It can occur alone or in association with other congenital defects and may be part of a syndrome. The sagittal suture is most commonly affected, comprising 40–60% of cases. Premature fusion of the sagittal suture can cause scaphocephaly due to compensatory anterior‐posterior growth of the skull. This is morphologically considered as a narrow elongated skull with a decreased cephalic index, and is diagnosed clinically and/or radiologically. Both the indications for surgery and the techniques used have varied with time and location. Surgical techniques have evolved, from limited craniectomy to calvarial remodeling. In recent times a return to craniectomy methods has occurred with the more recent introduction of endoscopic methods. Objectives : The objectives of this review were to identify and synthesize the best available evidence on the morphological, functional and neurological outcomes of craniectomy compared to cranial vault remodeling. Inclusion criteria : This review considered studies of infants with primary isolated sagittal synostosis operated on or before the mean age of 24 months. The intervention of interest was local craniectomy and this was compared to cranial vault remodeling. Morphological (primary), functional and neurological (secondary) outcomes were included. Mortality, complications and aesthetic outcome were included as tertiary outcomes. Methods : A comprehensive search was undertaken across major databases. The retrieved studies were assessed by two independent reviewers for methodological validity prior to inclusion. Data was then extracted and, where possible, pooled in statistical meta‐analysis. For descriptive studies, where statistical pooling was not possible, the findings are presented in narrative form. Results : Search and retrieval: Based on critical appraisal, 27 studies were considered to be suitable for this review. These studies were all descriptive in nature. Meta‐analysis was only possible for the primary morphological outcome (post‐operative cephalic index). Meta‐analysis Morphological (cephalic index): At one year follow‐up, post‐operatively remodeling offers an advantage over craniectomy (Z = 4.16, P<0.0001) Narrative summary Morphological: Improvements of the cephalic index to varying degrees were seen in patients receiving either procedure and there is not enough evidence to suggest that either treatment group had greater improvement over the other. Functional and neurological: Although their global scores may be comparable to an age‐matched population, patients with sagittal synostosis who have undergone a surgical repair of any type may have discrepancies in specific domains and may be at risk of developing learning disorders. There is insufficient primary research with inter‐procedure comparisons of preoperative and postoperative cognitive and neurological outcomes. Tertiary outcomes: There is not enough evidence to comment on mortality or postoperative infection in either treatment group. Patients undergoing cranial vault remodeling have a higher rate of transfusion compared to those undergoing craniectomy; however, it is likely that this difference relates to elective transfusion based on hospital‐specific protocols. It remains unknown whether there is an inherently higher need for transfusion in patients undergoing remodeling procedures. Delaying surgery however may increase the risk of raised intracranial pressure (ICP) and its associated complications. Whilst there is no evidence for raised ICP post‐craniectomy, a few studies have shown raised ICP in patients post‐remodeling. There is not enough evidence to establish a relationship between both procedures and raised ICP. Aesthetic outcome appears to be "better" in patients who undergo remodeling; however, there is little rigorous evidence to support this hypothesis. Conclusions : Conclusions were drawn from both the meta‐analysis and the narrative results. When comparing the mean change in cephalic index one year after surgery, remodeling was shown to be superior to limited craniectomy in patients with isolated synostosis of the sagittal suture. However both procedures were seen to give improvements at short, medium and longer term time points. Improvements in cephalic index may be sustained, deteriorate or improve over time; based on the current data neither procedure offers a clear long‐term advantage over the other. Longer follow‐up is required to compare outcomes at different time points. Patients who have surgery (any type) for isolated sagittal synostosis may have deficiencies in different subdomains at later school‐age testing, whilst maintaining an age‐appropriate global intelligence quotient (IQ) and school performance. There is no evidence to suggest that surgery of either type imparts any benefit in terms of functional or neurological outcomes. There is no evidence to suggest that surgery of either type imparts any benefit in terms of functional or neurological outcomes. While school performance and general IQ may be comparable to age‐matched controls, patients with sagittal synostosis who have undergone surgical repair of any type may be at risk of deficiencies in sub‐areas of testing and be at risk of learning disorders. There is insufficient evidence regarding mortality, infection, postoperative ICP and aesthetic outcome. While transfusion rates were greater in the remodeling group, this may be due to higher rates of elective transfusion. Implications for clinical practice and research The inconclusive findings indicate an ongoing need for higher quality primary research comparing the morphological and functional outcomes of craniectomy and cranial vault remodeling in primary sagittal synostosis. Outcomes should be measured in both the short and long term.